Development of Computer-Based Kindergarten Children's Creativity Portfolio Assessment Instruments - Marwah Nazhifah Sitorus; Anita Yus; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The problem in this study is that teachers still have difficulty assessing children's creativity, so the aim of this study is to develop a computer-based assessment instrument for the creativity portfolio of kindergarten children. This research is a Research and Development (R&D) using the ADDIE development model through 5 stages, namely: analyze, design, development, implementation and evaluation. Subjects in this study consisted of 3 teachers in Group A TK ABA 05 Medan. Then 6 validation experts who have the appropriate knowledge of this development research, among others: a) 2 assessment experts, b) 2 computer experts, c) 2 early childhood experts.  The determination of the feasibility level of the portfolio assessment instrument is based on the validation test of the experts, while the level of effectiveness of the portfolio assessment instrument is based on trials for teachers through teacher response questionnaires. Based on the results of the study, it was found that the assessment of the assessment expert validator I in this category was considered very valid with a percentage of 83% which means that it is very suitable for use and the second assessment expert in the category is considered very valid with a percentage of 83% which means very suitable for use. Then the computer expert I in the category is considered valid with a percentage of 81% which means it is suitable for use and the computer expert II in the category is considered very valid with a percentage of 86% which means very suitable for use. Furthermore, early childhood expert I in the very valid category with a percentage of 93% which means that it is very suitable for use and early childhood expert II in the category is considered valid with a percentage of 73% which means it is suitable for use. The results of the teacher response questionnaire on portfolio assessment using a gain score test with a value of 0.74 and can be categorized as high effectiveness, this indicates that the use of portfolio assessment instruments has been effectively used by TK ABA 05 Medan teachers.